A pilot study on the availability and reception of audio description in the Chinese mainland - Yang, Hui; Shen, Weiju; Liu, Bo; Wang, Yi (Frontiers in Communication, 2023)
Audio description (AD) is in its infancy in the Chinese mainland, both in terms of the provision of the service and as an academic object of study. This paper first provides a brief overview of the availability of AD in China and analyses difficulties encountered in its development. Then, it conducts a face-to-face questionnaire-based study on the reception of AD through a survey of 26 visually impaired persons. AD service in China is only limited to movies and there is a big gap between supply and demand. AD practice is facing many difficulties such as copyright constraints, low quality of AD services, lack of professionals and insufficient theoretical research. Our empirical research shows that the participants are quite satisfied with the quality of existing AD services, although they do not have a high level of comprehension of movies. Over interpretation, revealing the plot, subjective speculations are common practices in AD services in the Chinese mainland but are applauded by the participants for which helps them to understand the film.